Express your answer as a polynomial in standard form. f(x) = -x + 3 g(x) = 2x^2 – 3x – 7 Find: f(g(x))​

Question

Express your answer as a polynomial in standard form. f(x) = -x + 3 g(x) = 2x^2 – 3x – 7 Find: f(g(x))​

in progress 0
niczorrrr 6 months 2021-08-15T03:57:29+00:00 1 Answers 5 views 0

Answers ( )

    1
    2021-08-15T03:58:44+00:00

    Answer:

    -2x² + 3x + 10

    Step-by-step explanation:

    -(2x² – 3x – 7) + 3

    -2x² + 3x + 7 + 3

    -2x² + 3x + 10

Leave an answer

Browse

Giải phương trình 1 ẩn: x + 2 - 2(x + 1) = -x . Hỏi x = ? ( )